RELEVANSI MODEL BACAAN TERHADAP PERKEMBANGAN KEMAMPUAN BERPIKIR ANAK USIA SD - I Wayan Rasna (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
This research is intended to find out the forms of discourse, which are relevant to the develop¬ment of thinking abilities of the elementary school children of the third, fourth, fifth and sixth grades. For this purpose, experiment has been conducted in 8 (eight) elementary schools, covering 4 urban elemen¬tary schools and 4 city elementary schools. As a whole, there are 160 samples involved in this study. These samples are determined by making use of stratified random sampling technique. The data being collected in this first stage of research are in the forms of the ability in comprehending the content of reading text. These data were collected by means of test which were administered 48 times for every subject, within 24 weeks of experimentation. The data of the test were collected in the forms of interval data rates. For the purpose of completing the data, an interview as to the development of the children’s thinking ability in relation to the forms of discourse, in this case reading texts, was also carried out. The data were analyzed by using univariant statistical analysis and variant analysis. The result of the analysis shows that: (1) the forms of discourse (reading text) relevant to the development of thinking ability of the third grade of elementary school are narration; (2) the forms of discourse relevant to the fourth grade are narration and exposition; (3) for the fifth grade are exposition, description, and argumentation; (4) and for the sixth grade are a mixture of all forms of discourse or texts.